Neuromodulation by surface electrical stimulation of peripheral nerves for reduction of detrusor overactivity in patients with spinal cord injury: A pilot study. (March 2015) - Ojha, Rajdeep; George, Jacob; Chandy, Bobeena R.; Tharion, George; Devasahayam, Suresh R.
Abstract : Objectives: To demonstrate reduction in detrusor overactivity using surface electrical stimulation of posterior tibial nerve (PTN) or dorsal penile nerve (DPN) in patients with spinal cord injury (SCI). Design: Patients with SCI with symptoms of urinary urgency/leaks, with cystometrogram (CMG) proven detrusor overactivity were recruited in this study. Ten persons with observable F-wave from tibial nerve were included in the PTN group. Five persons who had F-wave absent but preserved bulbocavernosus reflex were included in the DPN group. Stimulation was given at 20 Hz, 10–40 mA for 20 minutes/session/day for 14 consecutive days. Detrusor overactivity was recorded using CMG on days 1 and 15. Settings: Rehabilitation Institute, Department of Physical Medicine and Rehabilitation, Christian Medical College and Hospital, Vellore, TN, India. Participants: Patients with SCI. Interventions: Surface stimulation of peripheral nerves for reduction of detrusor overactivity. Outcome measures: Qualitative analysis using voiding diary data and quantitative analysis using CMG data comparing pre- and post-intervention. Results: P value obtained from voiding chart was 0.021 for PTN and 0.062 for DPN. P value obtained from CMG data was not significant in both groups. In one subject, treatment was extended to 4 weeks and further improvement in voiding diary was seen. Conclusions: In this pilot study of 15 patients, voiding chart data showed statistically significant improvement following PTN stimulation and trend of improvement following DPN stimulation. However, the CMG data were not statistically significant in this sample population. Further studies with larger, appropriately powered sample size would be helpful to demonstrate the associations of symptoms with CMG data. Trial registration: CTRI no.; CTRI/2012/12/003234; CMCH Approval no.: CMC/IRB/6735/2008/12/18.